Targeting the Ras/Raf/MEK/ERK pathway in hepatocellular carcinoma - Yang, Sufang (Oncol Lett, 2017)
Although the biological basis of hepatocellular carcinoma (HCC) remains unclear, effective treatments and improvement of the survival rate remain worthwhile research goals. Abnormal protein signaling pathways contributing to uncontrolled cell proliferation, differentiation, survival and apoptosis are biomarkers of the carcinogenic process. Certain mutated components or overexpression of the rat sarcoma virus (Ras)/rapidly accelerated fibrosarcoma (Raf)/mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) signaling pathway are increasingly being studied in HCC carcinogenesis. The present review addresses the effect of the Ras/Raf/MEK/ERK signaling pathway on the pathogenesis of HCC, and provides an update on the preclinical and clinical development of various inhibitors targeting this core signaling pathway, which include various Ras inhibitors, Raf inhibitors and MEK inhibitors for HCC.